FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2015-2017 - Hendry Liman, Liana Susanto (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is for knowing the influence of firm size, leverage, firm age, and board size on firm performance in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study used a purposive sampling technique with 66 samples of manufacturing companies in Indonesia for 3 years from 2015-2017. Processing and testing of the data used in this study are Microsoft Excel 2007 and Eviews version 10. The results of this study state empirically that leverage has a positive influence on firm performance while firm size, firm age, and board size do not have an influence on firm performance. This study also has several recommendations which are explained in conclusions and suggestions regarding the results of this study.